EDITING OF EKA SABARA’S MANUSCRIPT “PARA ULAMA DAN TOKOH LOLOAN ABAD 19 MASEHI: SYARIF TUE DAN ENCIK YA’KUB”: A DOCUMENTATION OF LOLOAN ISLAMIC FIGURES IN JEMBRANA, BALI - Susie Chrismalia Garnida; Ni Ketut Mirahayuni (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2020)
Editing of Eka Sabara’s manuscript entitled Para Ulama dan Tokoh Loloan Abad ke-19 Masehi: Syarif Tue dan Encik Ya’kub (or in brief, Para Ulama dan Tokoh Loloan) is the second work of the efforts to document cultural legacy of the Loloan islamic community, of Jembrana, west Bali. This second manuscript focuses on the Loloan moslem figures of the 19th century, the time of which was thought to be the second landmark of the spread of Islamic faith and community in the area. In contrast to the first manuscript editing of the same author, i.e. of Eka Sabara’s Daeng Nachoda (2018), the editing of Para Ulama dan Tokoh Loloan manuscript involves significant addition of information to the original manuscript. The problems raised in the editing process comprises: (1) what are the characteristics of Eka Sabara’s manuscript entitled Para Ulama dan Tokoh Loloan?, and (2) what are editing strategies necessary to produce a coherent and cohesive text? The editing is based on Blanchard dan Root’s (1997) guides on editing academic texts, and content analysis method and editing techniques are conducted on the first draft (the manuscript) to suit the theme and purpose of the manuscript. The editing result shows that the manuscript needs to undergo major addition of chapters to meet the theme and to include other religious figures who also took part in the spread of Islamic faith and development of Loloan moslem community in Jembrana. Other editing techniques include addition, omission, rearrangement of information, all of which are used to produce a coherent, theme-suppporting text. The result of the editing process is a ready manuscript to be registered in the national library catalogue (with ISBN number) and then to be published as the document of a legacy of values and wisdom held and lived by the historical islamic figures in the Loloan community in Jembrana.